Respuesta :
Answer:
[tex]y=13x-35[/tex]
Step-by-step explanation:
Use the point-gradient form of a linear equation: [tex]y-y_1=m(x-x_1)[/tex]
(where [tex]m[/tex] is the gradient and [tex](x_1,y_1)[/tex] is a point on the line)
Given:
- [tex]m = 13[/tex]
- [tex](x_1,y_1)=(3,4)[/tex]
[tex]\implies y-y_1=m(x-x_1)[/tex]
[tex]\implies y-4=13(x-3)[/tex]
[tex]\implies y-4=13x-39[/tex]
[tex]\implies y=13x-35[/tex]
Answer:
[tex]y=13x-35[/tex]
Step-by-step explanation:
[tex]m=13[/tex]
[tex](x_{1},y_{1})=(3,4)[/tex]
[tex]y-y1=m(x-x1)[/tex]
[tex]y-4=13(x-3)[/tex]
[tex]y-4=13x-39[/tex]
[tex]y=13x-35[/tex]